Insulin‐regulated aminopeptidase inhibitor‐mediated increases in dendritic spine density are facilitated by glucose uptake. Issue 4 (16th October 2019) - Seyer, Benjamin; Diwakarla, Shanti; Burns, Peta; Hallberg, Anders; Grӧnbladh, Alfhild; Hallberg, Mathias; Chai, Siew Yeen
Abstract: Ethyl2‐acetylamino‐7‐hydroxy‐4‐pyridin‐3‐yl‐4H‐chromene‐3‐carboxylate (HFI‐419), the benzopyran‐based inhibitor of insulin‐regulated aminopeptidase (IRAP), has previously been shown to improve spatial working and recognition memory in rodents. However, the mechanism of its cognitive‐enhancing effect remains unknown. There is a close correlation between dendritic spine density and learning in vivo and several studies suggest that increases in neuronal glucose uptake and/or alterations to the activity of matrix metalloproteinases (MMPs) may improve memory and increase dendritic spine density. We aimed to identify the potential mechanism by which HFI‐419 enhances memory by utilizing rat primary cultures of hippocampal cells. Alterations to dendritic spine density were assessed in the presence of varying concentrations of HFI‐419 at different stages of hippocampal cell development. In addition, glucose uptake and changes to spine density were assessed in the presence of indinavir, an inhibitor of the glucose transporter 4 (GLUT4 ), or the matrix metalloprotease inhibitor CAS 204140‐01‐2. We confirmed that inhibition of IRAP activity with HFI‐419 enhanced spatial working memory in rats, and determined that this enhancement may be driven by GLUT4 ‐mediated changes to dendritic spine density. We observed that IRAP inhibition increased dendritic spine density prior to peak dendritic growth in hippocampal neurons, and that spine formation was inhibited when GLUT4 ‐mediated glucose uptake was blocked. In addition, during the peak phase of dendritic spine growth, the effect of IRAP inhibition on enhancement of dendritic spine density resulted specifically in an increase in the proportion of mushroom/stubby‐like spines, a morphology associated with memory and learning. Moreover, these spines were deemed to be functional based on their expression of the pre‐synaptic markers vesicular glutamate transporter 1 and synapsin. Overall, or findings suggest that IRAP inhibitors may facilitate memory by increasing hippocampal dendritic spine density via a GLUT4 ‐mediated mechanism. Cover Image for this issue: doi: 10.1111/jnc.14745 . Abstract : Inhibition of insulin‐regulated aminopeptidase (IRAP) activity improves spatial working and recognition memory in rodents. However, the mechanism of its cognitive‐enhancing effect remains unknown. There is a close correlation between dendritic spine density and learning in vivo . Here, we show that IRAP inhibition increases dendritic spine density via a glucose‐mediated process in vitro, which may facilitate memory in vivo . Cover Image for this issue: doi: 10.1111/jnc.14745 .